Pengelola Kurikulum dan Sarana Prasarana sebagai Penunjang Keberhasilan Pembelajaran Siswa Sekolah Dasar - Tri Puji Febrian; Lusia Dafa Ardiani; Nazhwa Nuzul Ahhani; Ira Dwi Lestari; Lisa Virdinarti Putra (Jurnal Bersama Ilmu Pendidikan (DIDIK), 2025)
Efforts to improve the effectiveness of children's learning at the Elementary School (SD) level can be driven by various elements, including the creation of an appropriate curriculum and the provision of adequate facilities. This study applies a literature study method with a qualitative approach, where the researcher serves as the main tool. Data were taken from various sources such as books, scientific articles in leading national and international journals, newspapers, and magazines. The findings of the study indicate that the success of the learning process is greatly influenced by efficient curriculum management. In addition, adequate facilities in schools greatly support the smooth running of the teaching and learning process. Curriculum management has an important role to ensure that learning objectives are achieved according to the predetermined schedule, as well as to compile detailed learning programs. Likewise, facility management also has an important function in supporting the implementation of programs that have been planned in the curriculum. Therefore, schools that are able to manage the curriculum and facilities well will be more successful in improving student learning outcomes.